A hospital-based cross-sectional study of clinical, wood's lamp, and dermoscopic findings in melasma - P M Amrutha Herle; Bhavana Ravindra Doshi (Wolters Kluwer Medknow Publications, 2023)
Background: Melasma is a common pigmentation disorder with female predominance. Depending on melanin depth, it can be epidermal, dermal, and mixed type. Assessment of this helps to chalk out a proper treatment plan. Dermoscopy is a device which helps to examine and assess pigment color and depth. Objective: Due to the relative dearth of literature on the correlation between clinical, dermoscopy, and Wood's lamp findings, we undertook this study to classify melasma and correlate dermoscopic features with clinical and Wood's lamp findings. Materials and Methods: Clinical, Wood's lamp, and dermoscopic examination with Dino-Lite Premier AM4113ZT were conducted in 160 patients of clinically diagnosed melasma. Findings of light-brown network and perifollicular sparing were considered for diagnosing epidermal melasma; gray-to-brown pigmentation, perifollicular or arciform pattern of hyperpigmentation for diagnosing dermal melasma. Patients with a combination of both were classified into mixed melasma. This was correlated with clinical and Wood's lamp findings. Results: Data analysis by statistical software R version 4.0.2 and Microsoft Excel showed female predominance (80%, n = 128). On clinical and Wood's lamp examination, the majority had mixed type of melasma; this was followed by epidermal and dermal melasma, respectively. Dermoscopic examination showed a mixed type of melasma in majority, followed by dermal and epidermal type. By Cohen's kappa, there was substantial agreement present between dermoscopic impression and Wood's lamp examination (K = 0.6112, P < 0.00001). Conclusion: Dermoscopic evaluation as a noninvasive tool provides a better insight on classifying the melasma patterns versus clinical and Wood's lamp examination and hence decides upon its further management.